Defining the nitrogen regulated transcriptome of Mycobacterium smegmatis using continuous culture. (December 2015) - Petridis, Michael; Benjak, Andrej; Cook, Gregory
Abstract Background Nitrogen is essential for microbial growth and its importance is demonstrated by the complex regulatory systems used to control the transport, assimilation and metabolism of nitrogen. Recent studies are beginning to shed light on how mycobacteria respond to nitrogen limitation and several regulators (e.g., GlnR, PII ) have been characterized at a molecular level. However, despite this progress, our knowledge of the transcriptional response of mycobacteria to nitrogen limitation and its regulation is confined to batch culture. Methods To gain further insight into the response of mycobacteria to nitrogen limitation, we developed a nitrogen-limited chemostat. We compared the transcriptional response of nitrogen-limited cells to carbon-limited cells using RNA-seq analysis in a continuous culture model at a constant growth rate. Conclusions Our findings revealed significant changes in the expression of 357 genes (208 upregulated, 149 downregulated; >2-fold change, false discovery rate <5 %) in response to nitrogen limitation in continuous culture. The vast majority of the GlnR regulon (68 %) was differentially expressed under nitrogen limitation in continuous culture and approximately 52 % of the 357 genes overlapped with a previously published study investigating the response ofM. smegmatis to nitrogen limitation in batch culture, while expression of only 17 % of the genes identified in batch culture were affected in our chemostat model. Moreover, we identified a unique set of 45 genes involved in the uptake and metabolism of nitrogen that were exclusive to our chemostat model. We observed strong downregulation of pathways for amino acid catabolism (i.e., alanine, aspartate, valine, proline and lysine), suggesting preservation of these amino acids for critical cellular function. We found 16 novel transcriptional regulators that were directly or indirectly involved in the global transcriptomic response ofM. smegmatis to nitrogen limitation and identified several non-coding RNAs that might be involved in the transcriptional or post-transcriptional regulation of nitrogen-regulated gene expression. Results Using nitrogen-limited continuous culture we identified the nitrogen-responsive transcriptome of M. smegmatis, including a number of small non-coding RNAs implicated in controlling nitrogen-regulated gene expression.